NETWORK-BASED EDUCATION - Aleksandr M. Kochnev (Высшее образование в России)
This paper describes new approaches to renew the methodology and content of KNRTU education process taking into account an interaction of education, science and industry. The paper represents the main principles of education process arrangement. Networking with Russian and foreign education and research institutions, as well as industrial companies, is emphasized for the purposes of education programs. The author underlines the importance of e-learning and distance education technologies.